2011
DOI: 10.1186/1743-422x-8-501
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of hospitalized patients with pandemic influenza A (H1N1) 2009 infections: the effects of bacterial coinfection

Abstract: BackgroundNumerous reports have described the epidemiological and clinical characteristics of influenza A (H1N1) 2009 infected patients. However, data on the effects of bacterial coinfection on these patients are very scarce. Therefore, this study explores the impact of bacterial coinfection on the clinical and laboratory parameters amongst H1N1 hospitalized patients.FindingsThis retrospective study involved hospitalized patients with laboratory-confirmed H1N1 infections (September 2009 to May 2010). Relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 9 publications
1
30
1
3
Order By: Relevance
“…A recent population-based study in the United States reported that M. pneumoniae was the most common bacterial pathogen in pediatric CAP (20). Dhanoa et al (21) reported that M. pneumoniae was the most common bacterial copathogen during the 2009 H1N1 pandemic. In the current study, the bacterium was the most common bacterial copathogen in influenza pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study in the United States reported that M. pneumoniae was the most common bacterial pathogen in pediatric CAP (20). Dhanoa et al (21) reported that M. pneumoniae was the most common bacterial copathogen during the 2009 H1N1 pandemic. In the current study, the bacterium was the most common bacterial copathogen in influenza pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of mixed viralbacterial infection identified in our study reflects the use of the serum biomarker PCT to augment comprehensive bacterial testing. In most previous studies reporting bacterial complications of viral infection, the bacterial testing was neither comprehensive nor systematic and frequently was left to the discretion of the clinician caring for the patient [26][27][28]. Although a number of clinical and laboratory variables were associated with mixed bacterial-viral infections, the absolute differences in individual variables from hospitalizations involving viral infection alone were small and unlikely to be helpful for patient management.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that there is considerable overlap in the comorbidities considered risk factors for both adverse pneumococcal disease outcomes and adverse influenza outcomes by ACIP [21,47], suggesting that these conditions associated with poor influenza outcome also increase risk in the presence of pneumococcal infection. If there are synergies between comorbidity and coinfection, as suggested by a study in Malaysia [10], the rate of coinfection may be overestimated; however we found that even when we halved our estimate of the rate of coinfection, vaccination remained cost-saving in an assumed pandemic similar to 2009–2010 H1N1.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies of H1N1-infected patients worldwide have confirmed high levels of bacterial coinfection, and there is evidence to suggest that bacterial coinfection led to excess H1N1 deaths. A retrospective analysis of hospitalized patients with laboratory-confirmed H1N1 in Malaysia found 14 of 50 patients (28%) to have a bacterial coinfection [10], and in a study of 199 H1N1-infected patients in Argentina, S . pneumoniae was detected in 56% of the 39 H1N1 cases that resulted in hospitalization or death [11].…”
Section: Introductionmentioning
confidence: 99%